Biodistribution of sodium pertechnetate and biochemical parameters in experimental osteoporosis in rats treated with extract of Chenopodium ambrosioides L (mastruz) - Soares, Ciro Dantas; Trindade, Sérgio Rodrigo Pereira; Sampaio, Tarciso Bruno Montenegro; Trindade-Neto, Cipriano Galvão da; Carvalho, Rejane Andrade de; Carvalho, Maria Goretti Freire de; Marques, Márcia Martins; Rêgo, Amália Cínthia Meneses; Araújo-Filho, Irami; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Objective: The aim of this study was to evaluate the effect of treatment with Chenopodium ambrosioides L (mastruz) hydroalcoholic extract in rats with osteoporosis on the biodistribution of sodium pertechnetate (Na99mTcO4) and biochemical parameters. Methods: Ten rats underwent ovariectomy to induce osteoporosis. The first group (n = 5) received no treatment, the second group (n = 5) received 50mg HaME for thirty days. After finishing the treatment the animals had been anesthetized and injected 0.1 mL (0.66 MBq) of Na99mTcO4 the femural vein. After 30 minutes, blood was collected for dosages, and then the animals were killed by an overdose of anesthetic (thiopental 100mg/kg) and removed the heart, lungs, stomach, femur, kidneys, liver, intestine and thyroid to calculate the percentage of radioactivity per gram of tissue (% ATI/ g) of each organ. Results: There was no significant difference in any of the organs analyzed, but in all of them, except in the intestine, the uptake of Na99mTcO4 was higher in the group treated with mastruz. Biochemical parameters showed a significant increase in lactate dehydrogenase, total cholesterol, and aspartate aminotransferase. These results allow us to state that mastruz may have hepatotoxic effect. Conclusion: Treatment with mastruz in rats with osteoporosis does not alter the biodistribution of the radiopharmaceutical Na99mTcO4 and showed some hepatotoxicity.